Optical communication base metal material and processing technology thereof

By combining nickel plating and hydrophobic coating on the surface of optical communication base metal materials, the problem of insufficient corrosion resistance and hydrophobicity of base materials in the prior art has been solved. This process achieves nickel plating and superhydrophobic coating with high hardness, low friction coefficient and excellent corrosion resistance, thereby improving the durability and self-cleaning properties of the base.

CN120989678APending Publication Date: 2025-11-21DONGGUAN ZHENGKUN PRECISION PROD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511129101.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-13
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing optical communication base metal materials are insufficient in terms of corrosion resistance, hydrophobicity, and surface properties, making it difficult to meet the requirements of varied installation environments.

Method used

By employing a combination process of nickel plating and hydrophobic coating, a nickel plating layer with high hardness, low friction coefficient and excellent corrosion resistance is prepared on the surface of the optical communication base substrate through specific formulations and processing steps of the plating solution and hydrophobic coating. A hydrophobic coating is then sprayed onto the plating layer to form a superhydrophobic coating.

Benefits of technology

It significantly improves the corrosion resistance and hydrophobicity of the base surface, enhances the base's alkali resistance, weather resistance and self-cleaning properties. The grain refinement of the nickel plating and the microstructure of the hydrophobic coating improve the surface smoothness and adhesion, achieving excellent durability and hydrophobicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure IMAGE_895CF2F4-244B-45F9-9066-B99B09EF8FE7
    Figure IMAGE_895CF2F4-244B-45F9-9066-B99B09EF8FE7
Patent Text Reader

Abstract

According to the optical communication base metal material and the processing technology thereof, the corrosion resistance and hydrophobic performance of the surface of a base can be effectively improved, so that the surface of the base metal material has excellent alkali resistance, weather resistance and self-cleaning performance; the Y (NO3) 3 is added, so that crystal grains grow in multiple directions, the growth of the crystal grains in a single direction is inhibited, the effect of refining the crystal grains is achieved, the fine crystal grains can fill gaps with one another, the microcosmic bulge height at a crystal boundary is remarkably reduced, and the surface flatness of a plating layer is improved; due to the organic polysilazane anchoring layer, the adhesive force of a hydrophobic modified substance on the surface of a base material is remarkably enhanced, and the durability of the hydrophobic modified substance is greatly improved; along with the increase of the content of the silicon dioxide nanoparticles, the orderliness of the rough structure on the surface of the coating is enhanced; due to the addition of the fluorine-containing modified trimethoxyhydrosilane which is a substance with low surface energy, the surface of the coating can show stronger hydrophobicity.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of stainless steel material, more particularly, the present application relates to a kind of optical communication pedestal metal material and its processing technology. BACKGROUND

[0002] Optical communication is a communication mode with light wave as carrier; according to light source characteristics, it can be divided into laser communication and non-laser communication; according to transmission medium, it can be divided into atmospheric laser communication and optical fiber communication. Optical fiber communication using laser as light source has the characteristics of not being disturbed by the outside world, good secrecy and wide range of use, and is suitable for long-distance large-capacity trunk digital communication on land and across the ocean; with the continuous improvement of the service life of semiconductor laser and the continuous reduction of optical fiber loss, various types of optical fiber communication system equipment are widely used. Optical fiber communication will develop towards long wavelength, ultra-low loss, single mode, dense wavelength division multiplexing, ultra-large capacity, optical integration, coherent heterodyne detection and all-optical communication without optical-electric conversion. The use of optical fiber has not only been used on land, and optical cables have been widely laid on the Pacific and Atlantic Ocean floor. The application of these submarine optical cables makes global communication very simple and fast.

[0003] The optical communication pedestal is the base part of the electronic components used for optical communication, mainly made of metal material, and the performance requirements of its surface are often more stringent due to the variable installation environment of the optical communication pedestal. SUMMARY

[0004] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present application provide an optical communication pedestal metal material and its processing technology.

[0005] An optical communication pedestal metal material, comprising an optical communication pedestal base, a nickel plating layer and a hydrophobic coating layer are arranged on the surface of the optical communication pedestal base, the hydrophobic coating layer is arranged on the outer side of the nickel plating layer, the nickel plating layer is made by electroplating the optical communication pedestal base with plating solution, and the hydrophobic coating layer is made by spraying the surface of the nickel plating layer with hydrophobic coating.

[0006] Further, the raw materials of the plating solution include: NiSO4·6H2O: 215-225 g / L, NiCl2·6H2O: 45-55 g / L, saccharin: 0.9-1.1 g / L, H3BO3: 43-47 g / L, Y(NO3)3: 0.35-0.45 g / L, and the rest is deionized water.

[0007] Further, the raw material of the hydrophobic coating includes fluorine-containing modified trimethoxysilane, polysilazane, silica nanoparticles and diatomite; the weight ratio of the fluorine-containing modified trimethoxysilane, polysilazane, silica nanoparticles and diatomite is (5.0-6.4):(13.3-15.3):(4.0-6.0):1.

[0008] Further, the raw material of the fluorine-containing modified trimethoxysilane includes trimethoxysilane, 2-(perfluorohexyl)ethyl methacrylate, Karstedt catalyst and tetrahydrofuran, the molar ratio of the trimethoxysilane and 2-(perfluorohexyl)ethyl methacrylate is (1.8-2.2):1, the amount of the Karstedt catalyst is 0.08-0.12% of the mass fraction of the 2-(perfluorohexyl)ethyl methacrylate, and the mass ratio of the tetrahydrofuran and trimethoxysilane is (3.5-4.5):1.

[0009] A processing process of an optical communication base metal material, and the specific processing steps are as follows: Step one: surface pretreatment is performed on the optical communication base substrate to obtain a pretreated optical communication base substrate; Step two: the pretreated optical communication base substrate is placed into a plating solution, a nickel ball with a purity of 99.9% is used as an anode, and the pretreated optical communication base substrate is used as a cathode to perform electroplating of nickel, and a nickel plating layer is formed on the surface of the pretreated optical communication base substrate; Step three: under the protection of nitrogen, tetrahydrofuran, trimethoxysilane and 2-(perfluorohexyl)ethyl methacrylate are sequentially added into a reaction container, after stirring uniformly, Karstedt catalyst is added, water bath stirring treatment is performed for 47-49h, heating is stopped, and rotary evaporation treatment is performed for 20-40min to obtain fluorine-containing modified trimethoxysilane in a milky white viscous state; Step four: the fluorine-containing modified trimethoxysilane and polysilazane are dissolved in trifluorotoluene, silica nanoparticles and diatomite are added, and after ultrasonic dispersion for 10-20min, a hydrophobic coating is obtained; Step five: the hydrophobic coating is added into a spray gun, the hydrophobic coating is uniformly sprayed on the surface of the nickel plating layer, after standing for 10-20min, drying and solidification treatment is performed for 5-7h to form a hydrophobic coating layer on the surface of the nickel plating layer, and an optical communication base metal material is obtained.

[0010] Further, in step one, the surface pretreatment method is plasma surface cleaning treatment or ultrasonic cleaning treatment.

[0011] Further, in step two, the pH of the plating solution is 3.5-4.5, the temperature is 45-55℃, the current density is 1.4-1.6A / dm 2 , and the time is 25-35min.

[0012] Further, in step three, the stirring speed is 560-640 r / min; and the water bath temperature is 75-85 DEG C.

[0013] Further, in step four, the weight ratio of the polysilazane and trifluorotoluene is 1: (40-50) ; the ultrasonic treatment power is 400-600 W, and the ultrasonic treatment frequency is 40-60 kHz.

[0014] Further, in step five, the spraying pressure is 0.25-0.35 MPa, the spraying distance is 13-17 cm, and during the drying and curing treatment, the drying treatment is carried out at 75-85 DEG C for 2-3 h, and the curing treatment is carried out at 115-125 DEG C for 2-3 h.

[0015] Technical effects and advantages of the present application: The optical communication base metal material prepared by the present application can effectively improve the corrosion resistance and hydrophobicity of the base surface, so that the base metal material surface has excellent alkali resistance, weather resistance and self-cleaning property; when the mass concentration of Y(NO3)3 in the plating solution in the nickel plating layer is 0.4 g / L, the comprehensive performance of the nickel plating layer is optimal, with high hardness, low friction coefficient and excellent corrosion resistance; the addition of Y(NO3)3 makes the crystal grains grow in multiple directions, inhibits the growth of the crystal grains in a single direction, and achieves the effect of grain refinement; the small crystal grains can fill the gaps by mutual filling, significantly reducing the micro-protrusion height at the grain boundary, thereby improving the flatness of the plating layer surface; the organic polysilazane anchoring layer significantly enhances the adhesion of the hydrophobic modified substance on the substrate surface and greatly improves its durability; the hydrophobic coating surface begins to appear micro-nano-scale protrusions and micron-scale pore structures, and the size and height of the micron-scale rough structure are also reduced, and the regularity of the surface rough structure is enhanced; as the content of the silica nanoparticles increases, the orderliness of the surface rough structure of the coating is enhanced, and the sub-micron or nano-rough structure also increases, and the prepared coating surface tends to form more regular and dense pore rough structures, providing good roughness for realizing super-hydrophobicity; the addition of the low-surface-energy fluorine-modified trimethoxysilane makes the coating surface exhibit stronger hydrophobicity. The surface of the optical communication base substrate is pretreated, which can effectively improve the cleanliness of the surface of the optical communication base substrate, and further effectively improve the adhesion stability and safety of the nickel plating layer; the pretreated optical communication base substrate is placed into a plating solution for electroplating treatment, and a nickel plating layer is formed on the surface of the pretreated optical communication base substrate; tetrahydrofuran, trimethoxysilane and 2-(perfluorohexyl) ethyl methacrylate are blended and stirred, and then a catalyst is added, water bath stirring and rotary evaporation are carried out to obtain fluorine-containing modified trimethoxysilane; the fluorine-containing modified trimethoxysilane and polymethyl hydrogen silazane (KH-OPZ115) are jointly added into trifluorotoluene, and then silica nanoparticles and diatomite are added, and ultrasonic dispersion treatment is carried out to obtain a hydrophobic coating; the hydrophobic coating is added into a spray gun, and then the hydrophobic coating is uniformly sprayed on the surface of the nickel plating layer, and then drying and curing treatment is carried out to form a hydrophobic coating on the surface of the nickel plating layer, thereby obtaining an optical communication base metal material. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the scope of protection of the present application.

[0017] Embodiment 1 The present application provides an optical communication base metal material, which comprises an optical communication base substrate, a nickel plating layer and a hydrophobic coating on the surface of the optical communication base substrate, the hydrophobic coating is arranged on the outer side of the nickel plating layer, the nickel plating layer is formed by electroplating the optical communication base substrate using a plating solution, and the hydrophobic coating is formed by spraying the surface of the nickel plating layer using a hydrophobic coating material. A processing technology of an optical communication base metal material, the specific processing steps are as follows: Step one: surface pretreatment (ultrasonic cleaning treatment) is performed on the optical communication base substrate to obtain a pretreated optical communication base substrate; Step two: the pretreated optical communication base substrate is placed into a plating solution, a nickel ball with a purity of 99.9% is used as an anode, and the pretreated optical communication base substrate is used as a cathode for electroplating nickel to form a nickel plating layer on the surface of the pretreated optical communication base substrate; the raw materials of the plating solution include: NiSO4·6H2O: 220 g / L, NiCl2·6H2O: 50 g / L, saccharin: 1.0 g / L, H3BO3: 45 g / L, Y(NO3)3: 0.35 g / L, and the rest is deionized water; the pH of the plating solution is 4.0, the temperature is 50℃, the current density is 1.5 A / dm 2 , and the time is 30 min; Step three: under the protection of nitrogen, tetrahydrofuran, trimethoxyhydrogen silane and 2-(perfluorohexyl) ethyl methacrylate were added into the reaction container in turn, after stirring, Karstedt catalyst was added, water bath stirring treatment was carried out for 48h, then heating was stopped, and rotary evaporation treatment was carried out for 30min, to obtain the fluorine-containing modified trimethoxy silane in a milky white viscous state; the molar ratio of trimethoxyhydrogen silane and 2-(perfluorohexyl) ethyl methacrylate was 2:1, the amount of Karstedt catalyst was 0.10% of the mass fraction of 2-(perfluorohexyl) ethyl methacrylate, the mass ratio of tetrahydrofuran and trimethoxyhydrogen silane was 4:1; the stirring speed was 600r / min; the water bath temperature was 80℃; Step four: the fluorine-containing modified trimethoxyhydrogen silane and polymethylhydrogen silazane (KH-OPZ115) were dissolved in trifluorotoluene, silica nanoparticles and diatomite were added, and after ultrasonic dispersion for 15min, the hydrophobic coating was obtained; the weight ratio of the fluorine-containing modified trimethoxyhydrogen silane, polymethylhydrogen silazane (KH-OPZ115), silica nanoparticles and diatomite was 5.0:13.3:4.0:1; the weight ratio of the polymethylhydrogen silazane (KH-OPZ115) and trifluorotoluene was 1:40; the ultrasonic treatment power was 500W, and the ultrasonic treatment frequency was 50kHz; Step five: the hydrophobic coating was added into the spray gun, the hydrophobic coating was uniformly sprayed on the surface of the nickel plating layer, and after standing for 15min, drying and curing treatment was carried out for 6h, to produce the hydrophobic coating on the surface of the nickel plating layer, and the optical communication base metal material was obtained; the spraying pressure was 0.30MPa, the spraying distance was 15cm, and during the drying and curing treatment, drying treatment was carried out at 80℃ for 3h, and curing treatment was carried out at 120℃ for 3h.

[0018] Example 2: Different from example 1, the raw materials of the plating solution included: NiSO4·6H2O: 220g / L, NiCl2·6H2O: 50g / L, saccharin: 1.0g / L, H3BO3: 45g / L, Y(NO3)3: 0.45g / L, and the rest was deionized water; the pH of the plating solution was 4.0, the temperature was 50℃, the current density was 1.5A / dm 2 , and the time was 30min.

[0019] Example 3: Different from examples 1-2, the raw materials of the plating solution included: NiSO4·6H2O: 220g / L, NiCl2·6H2O: 50g / L, saccharin: 1.0g / L, H3BO3: 45g / L, Y(NO3)3: 0.40g / L, and the rest was deionized water; the pH of the plating solution was 4.0, the temperature was 50℃, the current density was 1.5A / dm 2 , and the time was 30min.

[0020] Example 4: Different from Examples 1-3, the weight ratio of the fluorine-containing modified trimethoxysilane, polymethylhydrosilazane (KH-OPZ115), silica nanoparticles and diatomite is 6.4:15.3:6.0:1; the weight ratio of the polymethylhydrosilazane (KH-OPZ115) to trifluorotoluene is 1:50.

[0021] Example 5: Different from Examples 1-4, the weight ratio of the fluorine-containing modified trimethoxysilane, polymethylhydrosilazane (KH-OPZ115), silica nanoparticles and diatomite is 5.7:14.3:5.0:1; the weight ratio of the polymethylhydrosilazane (KH-OPZ115) to trifluorotoluene is 1:45.

[0022] Comparative Example 1: Different from Example 5, the optical communication pedestal metal material comprises an optical communication pedestal base body, and a nickel plating layer is arranged on the surface of the optical communication pedestal base body. A processing process of the optical communication pedestal metal material, and specific processing steps are as follows: Step one: performing surface pretreatment (ultrasonic cleaning treatment) on the optical communication pedestal base body to obtain a pretreated optical communication pedestal base body; Step two: placing the pretreated optical communication pedestal base body into a plating solution, taking a nickel ball with a purity of 99.9% as an anode and the pretreated optical communication pedestal base body as a cathode to perform electroplating of nickel, and electroplating a nickel plating layer on the surface of the pretreated optical communication pedestal base body; raw materials of the plating solution include: NiSO4·6H2O: 220 g / L, NiCl2·6H2O: 50 g / L, saccharin: 1.0 g / L, H3BO3: 45 g / L, Y(NO3)3: 0.2 g / L, and the rest is deionized water; the pH of the plating solution is 4.0, the temperature is 50°C, the current density is 1.5 A / dm2, and the time is 30 min. 2

[0023] Comparative Example 2: Different from Example 5, the optical communication pedestal metal material comprises an optical communication pedestal base body, and a nickel plating layer is arranged on the surface of the optical communication pedestal base body. A processing process of the optical communication pedestal metal material, and specific processing steps are as follows: Step one: performing surface pretreatment (ultrasonic cleaning treatment) on the optical communication pedestal base body to obtain a pretreated optical communication pedestal base body; ​Step two: put the pretreated optical communication pedestal substrate into the plating solution, take the nickel ball with the purity of 99.9% as the anode, and take the pretreated optical communication pedestal substrate as the cathode to electroplate nickel, and then a nickel plating layer is formed on the surface of the pretreated optical communication pedestal substrate; the raw materials of the plating solution include: NiSO4·6H2O: 220 g / L, NiCl2·6H2O: 50 g / L, saccharin: 1.0 g / L, H3BO3: 45 g / L, Y(NO3)3: 0.8 g / L, and the rest is deionized water; the pH of the plating solution is 4.0, the temperature is 50°C, the current density is 1.5 A / dm 2 , and the time is 30 min.

[0024] Comparative example 3: Different from example 5 is that: a processing technology of an optical communication pedestal metal material, and the specific processing steps are as follows: Step one: perform surface pretreatment (ultrasonic cleaning treatment) on the optical communication pedestal substrate to obtain a pretreated optical communication pedestal substrate; Step two: put the pretreated optical communication pedestal substrate into the plating solution, take the nickel ball with the purity of 99.9% as the anode, and take the pretreated optical communication pedestal substrate as the cathode to electroplate nickel, and then a nickel plating layer is formed on the surface of the pretreated optical communication pedestal substrate; the raw materials of the plating solution include: NiSO4·6H2O: 220 g / L, NiCl2·6H2O: 50 g / L, saccharin: 1.0 g / L, H3BO3: 45 g / L, Y(NO3)3: 0.40 g / L, and the rest is deionized water; the pH of the plating solution is 4.0, the temperature is 50°C, the current density is 1.5 A / dm 2 , and the time is 30 min. Step three: under the protection of nitrogen, tetrahydrofuran, trimethoxysilane and 2-(perfluorohexyl) ethyl methacrylate are sequentially added into a reaction container, after uniform stirring, Karstedt catalyst is added, water bath stirring treatment is performed for 48 h, heating is stopped, and then rotary evaporation treatment is performed for 30 min to obtain a milky white viscous fluorine-containing modified trimethoxysilane; the molar ratio of the trimethoxysilane and 2-(perfluorohexyl) ethyl methacrylate is 2:1, the amount of the Karstedt catalyst is 0.10% of the mass fraction of the 2-(perfluorohexyl) ethyl methacrylate, and the mass ratio of the tetrahydrofuran and the trimethoxysilane is 4:1; the stirring speed is 600 r / min; and the water bath temperature is 80°C. Step four: hydrophobic coating was obtained by dissolving fluorine-containing modified trimethoxysilane and polymethylhydrosilazane (KH-OPZ115) in trifluorotoluene, adding diatomite, and ultrasonic dispersion for 15 min; the weight ratio of fluorine-containing modified trimethoxysilane, polymethylhydrosilazane (KH-OPZ115) and diatomite was 5.7:14.3:1; the weight ratio of polymethylhydrosilazane (KH-OPZ115) and trifluorotoluene was 1:45; the ultrasonic treatment power was 500 W, and the ultrasonic treatment frequency was 50 kHz; Step five: the hydrophobic coating was added to the spray gun, the hydrophobic coating was uniformly sprayed on the surface of the nickel plating layer, and after standing for 15 min, drying and curing treatment was carried out for 6 h, a hydrophobic coating was prepared on the surface of the nickel plating layer, and an optical communication base metal material was obtained; the spraying pressure was 0.30 MPa, the spraying distance was 15 cm, and during the drying and curing treatment, drying treatment was carried out at 80℃ for 3 h, and curing treatment was carried out at 120℃ for 3 h.

[0025] The optical communication base substrate in the above examples and comparative examples was an aluminum alloy material (7A04(LC4) alloy), the polymethylhydrosilazane (KH-OPZ115) was purchased from the Institute of Chemistry, Chinese Academy of Sciences; the silicon dioxide nanoparticles were purchased from Dinghong Metal Material Co., Ltd., Nangong, brand: Dinghong, model: DH-SiO2; the trifluorotoluene was purchased from Shanghai Titan Science and Technology Co., Ltd.; the diatomite (DE MPs, particle size 200 mesh) was purchased from Shanghai Titan Science and Technology Co., Ltd.; the tetrahydrofuran was purchased from Nantong Runfeng Petroleum Chemical Co., Ltd., purity: 99%, brand: Runfeng; the trimethoxysilane was purchased from Shanghai Maier Biochemical Technology Co., Ltd.; the 2-(perfluorohexyl) ethyl methacrylate was purchased from Henan Weitixi Chemical Technology Co., Ltd., item number: A0144538; the Karstedt catalyst was purchased from Shanghai Yuan Ye Biological Technology Co., Ltd., item number: T25260.

[0026] The optical communication base metal materials in the examples and comparative examples in the present application were detected and treated: A contact angle measuring instrument (SDC-100, Dongguan Shengding Precision Instrument Co., Ltd.) was used to measure the water contact angle and the rolling angle; A 25mm×25mm coated layer was placed face to face with a 50g weight and sandpaper (1500 mesh), a transparent tape was attached to the back of the sample, and the sample was horizontally dragged on the sandpaper at a speed of 5mm / s through the tape; after every 40cm of wear distance, the water contact angle and the rolling angle of the coating were measured to prove its mechanical stability; after 360cm sandpaper friction test (load 50g); The sample was placed at a distance of 150mm from the 365nm ultraviolet light for 72h, and then the water contact angle and the rolling angle were tested, and the results are shown in Table 1: Table 1: ; The electrochemical test was carried out at room temperature by using Shanghai Chenhua CHI660E workstation. The corrosion resistance of the Ni plating layer was evaluated by Tafel curve and electrochemical impedance spectroscopy (EIS) test, the corrosion medium was 3.5% NaCl solution, the working electrode was the research sample (the test area was 1cm 2 ), the auxiliary electrode and the reference electrode were the same as above; the scanning rate of the Tafel curve test was 10mV / s, and the test interval was-0.5V~0V; the EIS test was carried out at the open circuit potential, the applied signal frequency was 100kHz to 10mHz, and the disturbance amplitude was ±5mV; the Tafel polarization curve of the Ni plating layer in 3.5% NaCl solution was obtained, the respective corrosion current density and corrosion potential were obtained by Tafel extrapolation method, and the results were shown in Table 2: Table 2: From the above table, it can be seen that the optical communication base metal material can effectively improve the corrosion resistance and hydrophobicity of the surface of the base, so that the surface of the base metal material has excellent alkali resistance, weather resistance and self-cleaning property. When the mass concentration of Y(NO3)3 in the plating solution in the nickel plating layer in the application is 0.4g / L, the comprehensive performance of the nickel plating layer is optimal, which has high hardness, low friction coefficient and excellent corrosion resistance; the addition of Y(NO3)3 will significantly increase the deposition overpotential, thereby reducing the critical nucleation energy of nickel crystal nucleus formation, promoting the increase of nucleation rate and crystal nucleus density, and finally forming a deposition layer with small crystal grains and dense structure; it is proved that the introduction of Y(NO3)3 and the increase of its mass concentration will not change the nucleation mode of nickel, but only affect the nucleation rate and growth rate of nickel grains on the cathode surface; when the mass concentration of Y(NO3)3 is increased to 0.4g / L, the plating layer crystal grains present long rhombus shape, and a small amount of flower bud-shaped clusters are accompanied, because Y 3+The Y(NO3)3 can be adsorbed on the surface of the electrode, so that the surface energy of the electrode is reduced, the nucleation sites are increased, and thus the Ni grain refinement is promoted; with the increase of the Y(NO3)3 concentration in the plating solution, the plated layer grain is continuously refined, the small grains can fill the gaps by mutual filling, the microscopic convex height at the grain boundary is significantly reduced, and thus the improvement of the flatness of the plated layer surface is realized; it can be seen that the increase of the Y(NO3)3 concentration changes the preferred orientation of the Ni plated layer, so that the grains grow along multiple directions, the grain growth along a single direction is inhibited, and the effect of grain refinement is achieved; with the increase of the Y(NO3)3 concentration, the corrosion potential of the Ni plated layer is first positively shifted and then negatively shifted, the corrosion current density is first reduced and then increased, that is, the corrosion resistance is first improved and then deteriorated; when the mass concentration of the Y(NO3)3 is 0.4 g / L, the corrosion potential of the Ni plated layer is the most positive, and the corrosion current is the lowest, indicating that the corrosion resistance is the best; the radius of the capacitive reactance arc of the nickel plated layer first increases and then decreases, and the radius of the capacitive reactance arc is the largest when the mass concentration of the Y(NO3)3 is 0.4 g / L, that is, the corrosion resistance is the best; the microhardness of the Ni plated layer increases with the increase of the Y(NO3)3 concentration, which indirectly indicates that the ability of the plated layer to resist external force deformation is enhanced; as the additive, the Y(NO3)3 can inhibit the growth of the Ni grains by increasing the nucleation rate, so that the grain size of the Ni plated layer is reduced, the surface flatness is improved, and the hardness is increased, so that the friction coefficient of the Ni plated layer is reduced; The organic polysilazane (OPSZ) in the application can occur condensation reaction with the hydroxyl group on the surface of the base material to form Si-O bond, thereby forming a stable chemical anchoring layer on the surface of the base material; the anchoring layer significantly enhances the adhesion of the hydrophobic modified substance on the surface of the base material and greatly improves the durability; the fluorosilane coupling agent and the OPSZ both belong to organosilicon compounds, and in the curing process, the two can form a stable Si-O-Si network structure through condensation reaction of silanol groups (-SiOH).The chemical cross-linking enables the fluorosilane coupling agent to form a uniform and stable composite coating after mixing with OPSZ, thereby significantly improving the thermal stability, chemical stability and mechanical durability of the coating; the silane coupling agent with fluorocarbon chain is generated by the reaction of 2-(perfluorohexyl) ethyl methacrylate and trimethoxysilane, the OPSZ is modified by fluorine through the mechanical mixing method, then the fluorine-modified OPSZ is uniformly mixed with nano-SiO2 particles and micron-SiO2 diatomite, and is sprayed on the surface of the nickel plating layer to construct an ultrahydrophobic coating; the bonding mechanism of the organic polysilazane and the surface of the substrate is as follows: the Si-N bond is opened, and finally condensed with the hydroxyl group on the surface of the substrate to form a Si-O bond, so as to be bonded to the surface of the substrate; the silane coupling agent is hydrolyzed to generate silanol, and then the silanol is condensed to form an oligomer containing Si-OH structure, then the oligomer forms a hydrogen bond with the hydroxyl group on the surface of the substrate, and finally the dehydration through heat treatment forms a covalent bond and is bonded to the surface of the substrate; the micro-nano level protrusions and micron level hole structures begin to appear on the surface of the hydrophobic coating, at the same time, the size and height of the micron rough structure are also reduced, and the regularity of the surface rough structure is also enhanced; the diatomite is coated or even embedded by a large amount of silica nanoparticles around, so that the combination of the two is more closely, at the same time, the protrusion structure with relatively sparse distribution and the cavity structure with different pore sizes and close arrangement are formed on the surface, and the regularity of the overall rough structure of the coating is also increased; with the increase of the content of the silica nanoparticles, the orderliness of the surface rough structure of the coating is enhanced, and the submicron or nano rough structure is also increased, and the surface of the prepared coating tends to form more regular and dense hole rough structure, which provides good roughness for realizing the ultrahydrophobicity of the coating; when the silica nanoparticles gradually participate in the formation of the microstructure, the coating surface gradually forms a regular micro-nano rough structure, and a large number of micro-nano level air cavity structures are formed on the surface of the coating when the coating contacts with water droplets, so that the coating realizes ultrahydrophobicity; the addition of the low surface energy substance fluorine-modified trimethoxysilane can make the coating surface exhibit stronger hydrophobicity; the hydrophobic coating still maintains high hydrophobicity after 10 times of adhesive tape peeling cycles; the water contact angle and rolling angle are tested after being placed at a position 150mm away from the 365nm ultraviolet light for 72h, and the ultrahydrophobicity is still maintained, which proves that the ultrahydrophobic coating can effectively resist outdoor solar ultraviolet rays; the micro-nano SiO2 particles are added to successfully prepare an ultrahydrophobic coating; although the ultrahydrophobic coating has weak stability in a strong acid (pH=1) environment, it has excellent alkali resistance, weather resistance and self-cleaning property. In step one, the optical communication base substrate is surface pretreated, which can effectively improve the cleanliness of the optical communication base substrate surface, and further effectively improve the adhesion stability and safety of the nickel plating layer; in step two, the pretreated optical communication base substrate is put into the plating solution for electroplating treatment, and the nickel plating layer is prepared on the surface of the pretreated optical communication base substrate; in step three, tetrahydrofuran, trimethoxysilane and 2-(perfluorohexyl) ethyl methacrylate are blended and stirred, then a catalyst is added, water bath stirring and rotary evaporation are carried out to obtain fluorine-containing modified trimethoxysilane; in step four, the fluorine-containing modified trimethoxysilane and polymethyl hydrogen silazane (KH-OPZ115) are jointly added into trifluorotoluene, then silica nanoparticles and diatomite are added, ultrasonic dispersion treatment is carried out to obtain a hydrophobic coating; in step five, the hydrophobic coating is added into a spray gun, then the hydrophobic coating is uniformly sprayed on the surface of the nickel plating layer, then drying and curing treatment is carried out, the hydrophobic coating layer is prepared on the surface of the nickel plating layer, and the optical communication base metal material is obtained.

[0027] Finally, it should be noted that: the above only for the preferred embodiments of the present application, and not for limiting the present application, although the foregoing detailed description of the present application is made with reference to the foregoing embodiments, for those skilled in the art, it still can be modified, or part of the technical features of the equivalent replacement. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application, should be included in the protection scope of the present application.

Claims

1. A metallic material for an optical communication base, characterized in that: The device includes an optical communication base substrate, the surface of which is provided with a nickel plating layer and a hydrophobic coating. The hydrophobic coating is located outside the nickel plating layer. The nickel plating layer is formed by electroplating the optical communication base substrate with a plating solution, and the hydrophobic coating is formed by spraying a hydrophobic paint onto the surface of the nickel plating layer.

2. The optical communication base metal material according to claim 1, characterized in that: The raw materials of the plating solution include: NiSO4·6H2O: 215-225 g / L, NiCl2·6H2O: 45-55 g / L, saccharin: 0.9-1.1 g / L, H3BO3: 43-47 g / L, Y(NO3)3: 0.35-0.45 g / L, and the remainder is deionized water.

3. The optical communication base metal material according to claim 2, characterized in that: The raw materials of the hydrophobic coating include fluorinated modified trimethoxysilane, polysilazane, silica nanoparticles and diatomaceous earth; the weight ratio of the fluorinated modified trimethoxysilane, polysilazane, silica nanoparticles and diatomaceous earth is (5.0-6.4):(13.3-15.3):(4.0-6.0):

1.

4. The optical communication base metal material according to claim 3, characterized in that: The raw materials for the fluorine-modified trimethoxysilane include trimethoxysilane, 2-(perfluorohexyl)ethyl methacrylate, Karstedt catalyst, and tetrahydrofuran. The molar ratio of trimethoxysilane to 2-(perfluorohexyl)ethyl methacrylate is (1.8–2.2):

1. The amount of Karstedt catalyst is 0.08–0.12% of the mass fraction of 2-(perfluorohexyl)ethyl methacrylate. The mass ratio of tetrahydrofuran to trimethoxysilane is (3.5–4.5):

1.

5. A processing technology for a metal material for an optical communication base, characterized in that: The specific processing steps are as follows: Step 1: Perform surface pretreatment on the optical communication base substrate to obtain the pretreated optical communication base substrate; Step 2: Place the pretreated optical communication base substrate into the plating solution, use nickel balls with a purity of 99.9% as the anode and the pretreated optical communication base substrate as the cathode to electroplate nickel, and electroplate a nickel coating onto the surface of the pretreated optical communication base substrate. Step 3: Under nitrogen protection, tetrahydrofuran, trimethoxysilane and 2-(perfluorohexyl)ethyl methacrylate are added sequentially to the reaction vessel. After stirring evenly, Karstedt catalyst is added and the mixture is stirred in a water bath for 47-49 hours. Heating is then stopped, and the mixture is rotary evaporated for 20-40 minutes to obtain a milky white viscous fluorinated modified trimethoxysilane. Step 4: Dissolve fluorine-modified trimethoxysilane and polysilazane in trifluorotoluene, add silica nanoparticles and diatomaceous earth, and disperse by ultrasonication for 10-20 minutes to obtain a hydrophobic coating. Step 5: Add the hydrophobic coating to the spray gun and spray it evenly onto the surface of the nickel plating. After standing for 10 to 20 minutes, dry and cure for 5 to 7 hours to form a hydrophobic coating on the surface of the nickel plating, thus obtaining the optical communication base metal material.

6. The processing technology of the optical communication base metal material according to claim 5, characterized in that: In step one, the surface pretreatment method is either plasma surface cleaning or ultrasonic cleaning.

7. The processing technology of a metal material for an optical communication base according to claim 5, characterized in that: In step two, the pH of the plating solution is 3.5–4.5, the temperature is 45–55℃, and the current density is 1.4–1.6 A / dm³. 2 Time: 25-35 minutes.

8. The processing technology of a metal material for an optical communication base according to claim 5, characterized in that: In step three, the stirring speed is 560–640 r / min; the water bath temperature is 75–85℃.

9. The processing technology of a metal material for an optical communication base according to claim 5, characterized in that: In step four, the weight ratio of polysilazane to trifluorotoluene is 1:(40-50); the ultrasonic treatment power is 400-600W; and the ultrasonic treatment frequency is 40-60kHz.

10. The processing technology of a metal material for an optical communication base according to claim 5, characterized in that: In step five, the spraying pressure is 0.25-0.35 MPa, the spraying distance is 13-17 cm, and the drying and curing treatment is carried out at 75-85℃ for 2-3 hours and at 115-125℃ for 2-3 hours.